Assisting the Design of Sensor and Information Fusion Systems - Mönks, Uwe; Trsek, Henning; Dürkop, Lars; Geneiß, Volker; Lohweg, Volker (2nd International Conference on System-integrated Intelligence)
The increased deployment of information technology for information processing, extensive networking, and system/environment monitoring using sensor and information fusion systems are essential characteristics of cyber-physical systems. They allow an autonomous recognition and evaluation of the system's status leading to autonomous reactions improving or maintaining the status to operate adaptively, robustly, anticipatory, and user-friendly. Assisting the operator in handling such complex systems is rather important and requires self-configuration, self-diagnosis, and self-optimization capabilities. In this paper, a new assisted design methodology for sensor and information fusion systems is proposed. It is based on an innovative system architecture consisting of the information fusion system itself, intelligent adaptable sensors, and the communication architecture of the "Intelligent Technical Systems OstWestfalenLippe" (it's OWL) Leading-Edge Cluster project "Intelligent Networking" providing an intelligent network for self-configuration and the required real-time data exchange.